A switched-capacitor bidirectional DC-DC converter with wide voltage gain range for electric vehicles with hybrid energy sources - Zhang, Yun; Gao, Yongpin; Zhou, Lei; Sumner, M. (Institute of Electrical and Electronics Engineers, 2018)
A switched-capacitor bidirectional DC-DC converter with a high step-up/step-down voltage gain is proposed for electric vehicles (EVs) with a hybrid energy source system (HESS). The converter presented has the advantages of being a simple circuit, a reduced number of components, a wide voltage-gain range, a low voltage stress, and a common ground. In addition, the synchronous rectifiers allow zero voltage switching (ZVS) turn-on and turn-off without requiring any extra hardware, and the efficiency of the converter is improved. A 300W prototype has been developed which validates the wide voltage-gain range of this converter using a variable low-voltage side (40V-100V) and to give a constant high-voltage side (300V). The maximum efficiency of the converter is 94.45% in step-down mode and 94.39% in step-up mode. The experimental results also validate the feasibility and the effectiveness of the proposed topology.